Spatio-Temporal Characteristics and Influencing Factors of Basic Public Service Levels in the Yangtze River Delta Region, China - Tianyu Li; Yizheng Zhao; Xiang Kong (Land, 2022)
Basic public services are essential to ensure regional social equity and promote regional integrated development. As the Yangtze River Delta region (YRDR) is an example of integrated regional development in China, the integration of basic public services plays a crucial role in promoting regions’ integrated development. However, little studies provide evidence of the characteristics and influencing factors of basic public services in the YRDR. Taking the YRDR as the study area, this paper constructed a comprehensive evaluation index system for the basic public services level (BPSL) in the YRDR from 2010 to 2020. Then, it measured and analyzed its spatio-temporal dynamic evolution characteristics using entropy-weighted TOPSIS and exploratory spatial data analysis methods, as well as analyzed the spatio-temporal heterogeneity of its influencing factors using a geographically and temporally weighted regression model. The results show that: (1) The BPSL in the YRDR generally improved during the study period. There was a huge variation within and between provinces in the BPSL. Over time, the BPSL gradually transitions from unipolar polarization to multipolar differentiation and a flattening trend. (2) Spatial differentiation of the BPSL was evident, with a decreasing gradient from east to west with an inverted U-shape distribution in the north–south direction. The overall spatial circle structure was characterized as being high in the east and low in the west, high in the center, and low in the north and south, forming a spatial distribution pattern of high-level and higher-level grades mainly in Shanghai, southern Jiangsu, and northern Zhejiang. The global spatial correlation characteristics became increasingly significant with time, while the local spatial correlation showed the trend of “spatial club convergence”. (3) Various factors influenced the spatial and temporal evolution of the BPSL, including the urbanization level, the economic development level, the industrial structure level, the degree of external openness, the government action capacity, and the regional population size, each of which had evident spatial and temporal heterogeneity.